2018
DOI: 10.3389/fmars.2018.00215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Dynamics and Availability in the Nearshore of Eastern Lake Erie: Insights From Oxygen Isotope Ratios of Phosphate

Abstract: Blooms of filamentous benthic algae that plagued Lake Erie in the 1950s through 1970s were largely reduced through reductions of phosphorus (P) loading from point sources.Since the mid-1990s, these blooms have returned despite a period of relatively stable external P inputs. While increased loadings of dissolved P have been causally linked to cyanobacterial blooms in some parts of the lake, the impacts of ecosystem changes such as the effect of invasive species on nutrient cycling and availability have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…(2016) indicated that there had been no significant change in overall annual TP loads over the past ∼25 yr. However, a profound re‐eutrophication of Lake Erie has occurred since the mid‐1990s, including cyanobacterial blooms in the western basin, hypoxia in the central basin, and resurgence of benthic algae in the eastern basin (Depew et al., 2018; Scavia et al., 2014).…”
Section: Lake Erie Water Quality Historymentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) indicated that there had been no significant change in overall annual TP loads over the past ∼25 yr. However, a profound re‐eutrophication of Lake Erie has occurred since the mid‐1990s, including cyanobacterial blooms in the western basin, hypoxia in the central basin, and resurgence of benthic algae in the eastern basin (Depew et al., 2018; Scavia et al., 2014).…”
Section: Lake Erie Water Quality Historymentioning
confidence: 99%
“…Although there have been reductions in P loads in some tributaries such as the Detroit River due to improvements by the Great Lakes Water Authority Water Resource Recovery Facility (see Scavia et al, 2019), Maccoux et al (2016) indicated that there had been no significant change in overall annual TP loads over the past ∼25 yr. However, a profound re-eutrophication of Lake Erie has occurred since the mid-1990s, including cyanobacterial blooms in the western basin, hypoxia in the central basin, and resurgence of benthic algae in the eastern basin (Depew et al, 2018;Scavia et al, 2014).…”
Section: Lake Erie Water Quality Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the methodology for direct determination has been developed in previous studies, , this method has not been widely adopted because of its complicated pretreatment for extracting and purifying phosphate in Org-P. Additionally, as isotopic fractionation factors are functions of the type of enzyme, the active extracellular enzymes responsible for the remineralization of DIP from Org-P should be clarified. Therefore, it was difficult to fix the δ 18 O value of DIP remineralized from the biosphere in previous studies. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was difficult to fix the δ 18 O value of DIP remineralized from the biosphere in previous studies. 10,13,14,29 In addition to δ 18 O, the Δ′ 17 O value [ = ln(δ 17 O + 1) − λ RL ln(δ 18 O + 1), detailed in Section 2.1] has been recently analyzed for some oxygen compounds to clarify the geochemical and biogeochemical processes on earth. 30−35 Substantial efforts to develop methodologies for the accurate and precise measurement of triple oxygen isotopes ( 16 O, 17 36 referred to as "mass-dependent" fractionation.…”
Section: Introductionmentioning
confidence: 99%